New Aryloxy-Quinone Derivatives with Promising Activity on Trypanosoma Cruzi - Segura-Segura, R; Segura-Segura, R; Pizarro-Reyes, J; Pizarro-Reyes, J (Wiley-VCH Verlag, 2020)
Continuing with a program to develop new quinone derivatives as biologically active compounds, we designed and synthesized a new series of aryloxy-quinones, which were evaluated in vitro against Trypanosoma cruzi in epimastigote form. Chemical modifications in three specific moieties on the aryloxy-quinone core were considered for developing new anti-T. cruzi agents. The majority of our new quinones showed higher potency (IC50 values of <0.70 µM) than nifurtimox, a known pharmaceutical used as a baseline drug (IC50 values of 7.00 µM); however, only two of them elicited higher selectivity than nifurtimox against Vero cells. A structure–activity relationship analysis provided information about the stereoelectronic features of these compounds, which are responsible for an increase in trypanosomicidal activity. Using a pharmacophore model, we mapped the substitution patterns of the five pharmacophoric features of trypanosomicidal activity. We chose the Epc1 compounds and found no relationship with the trypanosomicidal effects. These results provided useful information about the structural characteristics for developing new aryloxy-quinones with higher potency against the protozoan parasite T. cruzi. © 2019 Deutsche Pharmazeutische Gesellschaft